(untitled) (Asian Journal of Ethnobiology, 2022)
Abstract. Nurshillah C, Anggorowati D, Putri ER, Balgis M, Nurwulandari M, Murtiningsih, Agustina N, Wulandari P, Liza N, Himawan W, Setyawan AD. 2022. Diversity of edible plants traded in Legi Traditional Market, Surakarta, Indonesia. Asian J Ethnobiol 5: 52-61. A traditional market is used to conduct buying and selling transactions conducted by direct bargaining. The market is used as a center of socioeconomic activities and a social heritage representation. Many commodities are commonly traded in traditional markets, such as staple foods and other edible plant products such as vegetables, spices, tubers, and fruits. Some of them also have additional functions as herbal remedies. This research aims to inventory edible and medicinal plant species traded in the traditional market in Surakarta, Central Java, Indonesia, namely Legi Market. The method used in this research is the qualitative descriptive method. Direct research observations, including plant surveys and in-depth interviews with Legi Market traders, are used to collect the data. The results showed that the Legi market plays a vital role in the availability of the crops produced by village farmers. There are 92 species of edible plants recorded in the Legi Market, predominately with the Fabaceae group. Furthermore, leaf products were identified as the most commercialized plant parts. In terms of medicinal purposes, 17 species were listed to be used as treatment agents, with the rhizome being the most functioned part.